2022
DOI: 10.3390/cancers14030721
|View full text |Cite
|
Sign up to set email alerts
|

Incident Colorectal Cancer in Inflammatory Bowel Disease

Abstract: Colorectal cancer (CRC) risk is increased in Inflammatory Bowel Disease (IBD) and surveillance needs to be tailored according to individual risk. The open issues include the role of the characteristics of IBD and CRC in determining the long-term outcome. These issues were assessed in our multicenter study, including a cohort of 56 IBD patients with incident CRC. The clinical and histopathological features of IBD patients and of CRC were recorded. Incident CRC in IBD occurred at a young age (≤40 years) in 25% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This further supports the need for tailored surveillance programs aimed to prevent or allow a timely diagnosis of CRC, most often mimicking IBD-related symptoms. Accordingly, our previous multicenter study reported an overall low frequency of symptomatic CRC in IBD, thus also highlighting the issue of appropriate CRC surveillance in tertiary IBD referral centers [34].…”
Section: Discussionmentioning
confidence: 79%
“…This further supports the need for tailored surveillance programs aimed to prevent or allow a timely diagnosis of CRC, most often mimicking IBD-related symptoms. Accordingly, our previous multicenter study reported an overall low frequency of symptomatic CRC in IBD, thus also highlighting the issue of appropriate CRC surveillance in tertiary IBD referral centers [34].…”
Section: Discussionmentioning
confidence: 79%
“…Anti-TNFα agents, particularly ADA, followed by UST and VED, play a role in the onset of dermatological pathologies, including urticaria, erythema, and dermatitis [ 57 ]; moreover, our data showed a higher incidence of malignancies with VED when adjusted on 10 years of treatment. Chronic inflammation is more frequently related to colorectal cancer development and extraintestinal neoplasms in IBD patients than in the general population [ 58 , 59 ]. Nevertheless, immunosuppressive treatment, including biologics, exhibit carcinogenic properties [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is increased risk of intestinal cancer in CD patients 6,27 . A meta‐analysis, which was based on six Western population studies showed an increased risk of intestinal cancer in CD (SIR 1.9; 95% CI, 1.4–2.5) 28 .…”
Section: Temporal Trend Of CD Surgical Rate Indications and Methodsmentioning
confidence: 99%
“…26 It is known that there is increased risk of intestinal cancer in CD patients. 6,27 A meta-analysis, which was based on six Western population studies showed an increased risk of intestinal cancer in CD (SIR 1.9; 95% CI, 1.4-2.5). 28 In Asia, only a few population-based studies have examined the association between IBD and CRC development.…”
mentioning
confidence: 99%